2011
DOI: 10.1039/c0ee00629g
|View full text |Cite
|
Sign up to set email alerts
|

Optimal process design for the polygeneration of SNG, power and heat by hydrothermal gasification of waste biomass: Thermo-economic process modelling and integration

Abstract: This paper presents a process model for the polygeneration of Synthetic Natural Gas (SNG), power and heat by catalytic hydrothermal gasification of biomass and biomass wastes in supercritical water. Following a systematic process design methodology, thermodynamic property models and thermoeconomic process models for hydrolysis, salt separation, gasification and the separation of CH 4 , CO 2 , H 2 and H 2 O at high pressure are developed and validated with experimental data. Different strategies for an integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 34 publications
(98 reference statements)
1
94
0
Order By: Relevance
“…The model determines the species conversion and calculates the associated heat and power balances. A detailed description of the considered model was published by Gassner et al (2011). Then, an energetic-economic-environmental model is constructed in the OSMOSE platform (OSMOSE, 2013).…”
Section: Computational Optimization Methodologymentioning
confidence: 99%
“…The model determines the species conversion and calculates the associated heat and power balances. A detailed description of the considered model was published by Gassner et al (2011). Then, an energetic-economic-environmental model is constructed in the OSMOSE platform (OSMOSE, 2013).…”
Section: Computational Optimization Methodologymentioning
confidence: 99%
“…The SOFC outlet stream is at high temperature and still contains some syngas. Thus it has a high exergy content, which is exploited Hydrothermal gasification (HTG) (Gassner et al, 2011) 100 -65 -5 -Gasification and methanation (Bio-SNG) (Gassner and Maréchal, 2012) 100 -69.3 -3.7 -Bio-SNG and electrolysis (Gassner and Maréchal, 2008) 100 144.5 170 ---Fischer-Tropsch synthesis (FT) (Emanuela, 2015) 100 1.64 43.3 ---FT and electrolysis (Emanuela, 2015) 100 54.2 84.2 ---Integrated gasifier-SOFC-GT System (CFB-SOFC-GT) (Caliandro et al, 2014) 100 ---71 -CFB-SOFC-GT with CCS (CFB-SOFC-GT and CCS) (Caliandro et al, 2014) 100 ---67.8 b -Biomass integrated gasification combined cycle (BIGCC) (Sthl and Neergaard, 1998) 100 --49 32 -Torrefaction (Peduzzi et al, 2014) 100 --25 60 -Hybrid cycle SOFC and gas turbine (SOFC and GT) (Facchinetti et al, 2011) 100 --16 80 -SOFC and GT with CCS (SOFC and GT and CCS) (Facchinetti et al, 2011) 100 --16 77.8 b -Combined cycle gas turbine (CCGT) (Bauer et al, 2008) 100 ---63 -CCGT with CCS (CCGT and CCS) (Bauer et al, 2008) 100 ---57 -Supercritical plant (Bauer et al, 2008) 100 in a gas turbine to produce additional electricity (Facchinetti et al, 2011). If the combustion in the gas turbine is made with pure oxygen, the flue gases only contain CO2 and water vapor.…”
Section: Integrated Gasifier-sofc-gt System For Electricity Productionmentioning
confidence: 99%
“…An alternative to the use of wood as carbon source consists in capturing the CO2 directly from the atmosphere, but the electricity-to-fuel efficiency then drops to 52% (Parra et al, 2017). Hydrothermal gasification (HTG) is a promising technology for the production of bio-SNG from wet woody biomass or any biomass with moisture content between 50 and 80% (Gassner et al, 2011). As for the gasification/methanation process, HTG fully converts the energy content of the biomass into gas, electricity, and heat.…”
Section: Gasification and Methanation For Bio-sng Productionmentioning
confidence: 99%
“…Recently, studies have examined the isolation of other factors such as feedstock morphology to better understand the added-value of catalytic treatment [17]. It is worth to mention that experimental findings have reported that for non-catalytic processing, 330 °C and 210 bar present more favorable conditions for Biocrude yield [12].…”
Section: Introductionmentioning
confidence: 99%
“…Active hydronium [H3O] + and hydroxyl [OH] -ions, as a result of the higher ionic water product pKw in subcritical conditions, take part as a reactant or catalyst for the cleavage of carbon-hetero bonds [4]. The extracted nitrogen and sulphur compounds from the solid feed are distributed along the multi-phase products, and are reduced heavily within the Biocrude [12]. In the case of oxygen, it is removed in the form of either water (H2O) through dehydration or CO2 through decarboxylation, the two are competing pathways but both with positive effects [9].…”
Section: Introductionmentioning
confidence: 99%